Differences in quality of life improvement with pulmonary vein isolation alone vs. more extensive ablation of persistent atrial fibrillation: insights from the EARNEST-PVI trial. (14th October 2021) - Kanda, T; Masuda, M; Inoue, K; Furukawa, Y; Hirata, A; Egami, Y; Watanabe, T; Minamiguchi, H; Miyoshi, M; Matsuda, Y; Sunaga, A; Sotomi, Y; et al.
Abstract: Background: Improving the quality of life (QoL) is one of the main purposes of catheter ablation (CA) of persistent atrial fibrillation (AF). QoL improvement in persistent AF patients has not been fully clarified. The EARNEST-PVI trial was a multi-center randomized trial comparing clinical outcomes of pulmonary vein isolation (PVI) alone and more intensive ablation in addition to PVI including complex fractionated atrial electrogram (CFAE) and linear ablation (PVI plus). Purpose: To investigate the QoL change after persistent AF ablation and the differences between the PVI-alone strategy and the PVI plus strategy. Methods: In the EARNEST-PVI trial, patients with persistent AF who underwent an initial catheter ablation (n=512) were randomly assigned in a 1:1 ratio to either PVI alone or PVI plus. Quality of life was assessed at baseline and at 12 months after ablation for AF using the 36-Item Short Form Health Survey. Scores were also converted to a physical health component summary (PCS), a mental health component summary (MCS) and a role/social component summary (RCS). Results: In the EARNEST-PVI trial, the PVI alone strategy was associated with higher recurrence rate compared with the PVI plus additional ablation strategy. After excluding 68 patients for whom preoperative or postoperative QoL assessment was not available, 222 patients were evaluated respectively. Overall, significant improvements in PCS (46.2±11.4 to 48.7±11.4]), MCS (50.1±8.8 to 54.3±8.6) and RCS (44.6±13.3 to 48.6±11.3) occurred 12 months after ablation (P<0.001, respectively). Although significant QoL improvement occurred in both PVI alone and PLI plus strategies, the changes in PCS was greater in the PVI-plus than that in PVI-alone (3.5±10.3 vs 1.5±10.6, P=0.04). Conclusions: Ablation for persistent atrial fibrillation improved both physical and mental quality of life. The PVI-plus strategy showed greater improvement in physical QoL. Funding Acknowledgement: Type of funding sources: None.